Repositioning of Female Children's Inheritance in Indonesia Through Jurisprudence in the Perspective of Mubadalah Theory - Al-Fitri; Aulia Rahman Iskandar; A. Zamakhsyari Baharuddin (Journal of Islamic Mubadalah, 2025)
Although Indonesia has made legal reforms in the field of inheritance, in practice there are nevertheless problems with the position of girls. The role of Religious Court judges is very large in providing protection for the inheritance rights of girls. If there is a division of inheritance that is treated discriminatory, judges must dare to make breakthroughs in reform. The goal is so that the position and status of inheritance of girls does not experience discrimination. This issue is interesting because some inheritance teachings differentiate between boys and girls, so that they have received criticism from women activists, although from Islamic law experts. This study aims to determine the arguments of the Supreme Court in interpreting the word walád. The method used is qualitative, with a normative approach, which is analyzed using the mubádalah theory, which emphasizes the distribution of inheritance on the principles of cooperation, mutuality, reciprocity and gender justice. The results of this study indicate that jurisprudence has responded to equality between boys and girls in the contemporary inheritance system, although in its application it has not been fully followed by Religious Court judges. In determining the position of heirs, it is no longer based on gender, therefore must be repositioned on the basis of the closeness of the bloodline relationship between the heir and the testator.